2019
DOI: 10.25225/fozo.015.2019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonality, environmental and anthropic factors on crop damage by wild boar Sus scrofa

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In most cases, the prevention methods, where and when adopted, are applied after the damages have already occurred, and without a cost-benefit analysis (Massei et al 2011;Meriggi et al 2016). The formulation of risk prediction models allows acting in advance by assigning a risk class to each field and therefore to identify the fields most at risk (Cappa et al 2019), where it is possible to provide deterrent systems such as electrified fences or acoustic deterrents. This would improve the effectiveness of these tools and could partially reduce their economic impact on single farms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the prevention methods, where and when adopted, are applied after the damages have already occurred, and without a cost-benefit analysis (Massei et al 2011;Meriggi et al 2016). The formulation of risk prediction models allows acting in advance by assigning a risk class to each field and therefore to identify the fields most at risk (Cappa et al 2019), where it is possible to provide deterrent systems such as electrified fences or acoustic deterrents. This would improve the effectiveness of these tools and could partially reduce their economic impact on single farms.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding activity of wild boar in cultivated fields can be analyzed from the perspective of the general predictions of the optimal foraging theory, trying to identify which factors related to energy intake, energy expenditure and animal safety contribute to the choice of fields in to go to for food (Stephen and Krebs 1986;Krebs and Kalcenik 1991;Begon et al 2006;Rubenstein and Alcock 2018). Through the analysis of the factors that influence the occurrence of damage, it is possible to formulate predictive risk models that allow to identify the most threatened areas and to act before the damage occurs with prevention tools (Ficetola et al 2014;Lombardini et al 2017;Cappa et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Calenge et al (2004) showed that diversionary feeding practices significantly reduced wild boar damage, suggesting that food availability had a major influence on the likelihood and extent of damage caused to crops. However, diversionary feeding can increase ungulates’ reproductive output, carrying capacity and hence population size (González‐Crespo et al 2018, Cappa et al 2019).…”
Section: Methods and Contexts Of Overabundancementioning
confidence: 99%
“…Wild boar (Sus scrofa) is a native species widely distributed from Europe to Asia (Keuling and Leus 2019) that can negatively impact ecosystems of introduced areas as an invasive species (Barrios-Garcia and Ballari 2012, Risch et al 2021). Wild boars have been reported to cause crop damage (Lombardini et al 2017, Cappa et al 2019) and human injuries (Mayer 2013) and are vectors causing infectious diseases in humans and livestock (Antolová et al 2007, Gortázar et al 2007). Thus, wild boar population management is essential to control the damage caused by them.…”
Section: Introductionmentioning
confidence: 99%